Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Femmes noires francophones: une réflexion sur le patriarcat et le racisme aux XXe-XXIe siècles - Angone, Odome (Collection Kala éditions, 2020)
"Sous l'égide symbolique du soixantenaire des Indépendances Africaines, Femmes Noires Contemporaines livre une réflexion subsaharienne sur le patriarcat et le sexisme aux XXe-XXIe siècles. L'ouvrage, fort de nombreux témoignages récents de femmes, est nourri par des questionnements, des enjeux et des interpellations collectives liées à une époque où, sans plus déléguer leur parole à des intermédiaires ou des médiateurs, les femmes ont désormais leur mot à dire sur des questions qui les concernent directement. Parler de LA femme noire et africaine, c'est révéler l'histoire de ces innombrables vies contraintes et de ces voix réduites au silence, de ces ferveurs et ces rêves étouffés, de ces existences confinées, délimitées par des frontières imposées. L'auteure dresse ici le portrait de cette femme, reléguée dans un ghetto hors du temps, à qui le racisme et le patriarcat contestent le droit à la parole, à qui on dénie le droit élémentaire et légitime de parler en son nom propre."
Keywords: OFDIG; afrique; afro-féminisme; approches et analyses; discipline; femmes* noires; féminisme africain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; patriarcat; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; systèmes d'oppressions; thématiques

Book Launch: Decolonization and Afro-Feminism - Firoze Manji (2020)
Sylvia Tamale, author of Decolonization and Afro-Feminism, will be discussing her new book with Charmaine Pereira, writer and feminist scholar in Abuja, Nigeria. Host: Firoze Manji, Publisher, Daraja Press September 24, 2002
Keywords: afrique; afro-féminisme; approches et analyses; cours; fem3300; féminisme africain; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions

Carthographie des militantismes afros en contexte français - Gabriel, Joao (Le blog de Joao, 2019)
Image : tableau de Joseph Amedokpo, peintre togolais. Une version en anglais de ce texte a été publiée dans le numéro 20 de la revue The Funambulist, paru en Novembre 2018, sous le titre Present and Future of Afro activism in France. L’objectif était de dresser un portrait des mobilisations afros, en particulier celles qui ont été médiatiquement relayées, dans le contexte français. J’ai écrit cela à destination d’un lectorat étranger qui comme souvent risque d’avoir une approche très états-unienne de ce qu’est la « question noire ». C’était alors l’occasion de présenter, sans évidemment prétendre à l’exhausitivité, ce qui se passe en France côté afro, dans un article court pour cette revue qui aborde de façon plus générale les questions relatives au colonialisme et aux luttes contre lui.
Keywords: afrique; afro-descendant.e.s; approches et analyses; cours; europe; fem3300; france; premier cycle; racisme; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Les femmes musulmanes et le « droit de choisir librement » - Abu-Lughod, Lila (Anthropologie et Sociétés, 2018)
Tout en soulignant qu’il s’avère illusoire de vouloir séparer les situations personnelles des conditions historiques et politiques de leur émergence, cet article propose une réflexion critique de la notion de libre choix, que l’auteure inscrit dans un réseau de facteurs macrosociaux tels que les tensions internationales ou encore la violence et la pauvreté structurelles. La notion de « libre choix » possède une charge idéologique qui se reflète dans la distinction souvent établie entre les femmes occidentales libérées et la femme musulmane dépourvue de libre choix et victime passive de l’oppression patriarcale. Le libre choix tend aujourd’hui à (re)devenir un critère discriminatoire permettant de distinguer les sociétés les « plus civilisées » (choix et liberté pour les « Occidentales ») de celles qui le sont moins (contrainte et servitude pour les « Orientales »). La violation du libre choix des femmes peut alors contribuer à légitimer l’intervention des industries humanitaire et militaire pour « sauver les musulmanes », comme cela a été le cas dans la guerre d’Afghanistan, à la suite des événements tragiques du 11 septembre 2001. Qui a le pouvoir de réduire « l’Autre », et particulièrement les musulmanes, à des sujets assujettis incapables d’émerger comme sujets agissants ? Des musulmanes souffrent d’un libre choix limité, mais ceci est-il réductible à l’islam ? Le libre choix des Occidentales relève-t-il d’un idéal fantasmé ? Faudrait-il plutôt investiguer la notion de libre choix dans sa complexité intrinsèque reliée aux relations de pouvoir ? Réduire les vies poignantes et tellement complexes des femmes musulmanes à une question de choix plus ou moins libre et éclairé est d’une totale insatisfaction pour l’anthropologue. Afin de mieux saisir cette complexité, l’auteure puise dans son travail ethnographique s’échelonnant sur une vingtaine d’années en milieu rural égyptien pour souligner l’importance du travail (micro)ethnographique qui permet de dépasser les généralités et les simplicités galvaudées par certains médias et romans à sensation (« pulp nonfiction ») qui font et défont l’opinion publique. L’auteure compare ces généralités essentialisantes avec des exemples de vies socialement complexes et ethnographiquement riches de villageoises égyptiennes.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; féminisme décolonial; féminisme islamique; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; égypte

Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Jade Almeida - Almeida, Jade (2018)
Originaire de Guadeloupe, Jade Almeida intervient tous les jeudis sur la web radio Neoquebec et participe à divers projets mettant les femmes noires au centre de la narration. Elle se positionne contre la négrophobie et la misogynie noire et tente de naviguer l’institution académique dans une optique de décolonisation.
Keywords: afrique; afro-féminisme; amériques; approches et analyses; canada; caraïbes; cours; discours dominant; europe; fem3100; france; féminismes noirs; identités LGBTQIA2+; misogynoir; premier cycle; québec; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Décoloniser l’islam contre le pouvoir, l’hégémonie et toutes les formes d’exploitation - Esack, Farid (Tumultes, 2017)
Né dans les faubourgs du Cap, et actuellement professeur d’Études islamiques à l’Université de Johannesburg, en Afrique du Sud, Farid Esack est l’un des représentants les plus marquants du courant musulman de la théologie de la libération. Militant anti-apartheid, il avait été en charge de la Commission pour l’égalité homme-femme dans le gouvernement de Nelson Mandela. Il est l’auteur de nombreux ouvrages, dont Qur’an Liberation and Pluralism (1997), dans lequel il défend l’idée d’une solidarité interreligieuse contre toutes les formes d’oppression, ainsi que de Coran, mode d’emploi (Albin Michel, 2004).
Keywords: afrique; afrique du sud; approches et analyses; cours; discours dominant; entretien; fem3400; islam; premier cycle; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions

Le ventre des femmes : capitalisme, racialisation, féminisme - Vergès, Françoise (Albin Michel, 2017)
Dans les années 1960-1970, l'État français encourage l'avortement et la contraception dans les départements d'outre-mer alors même qu'il les interdit et les criminalise en France métropolitaine. Comment expliquer de telles disparités? Partant du cas emblématique de La Réunion où, en juin 1970, des milliers d'avortements et de stérilisations sans consentement pratiqués par des médecins blancs sont rendus publics, Françoise Vergés retrace la politique de gestion du ventre des femmes, stigmatisées en raison de la couleur de leur peau. Dès 1945, invoquant la «surpopulation» de ses anciennes colonies, l'État français prône la régulation des naissances et l'organisation de l'émigration; une politique qui le conduit à reconfigurer à plusieurs reprises l'espace de la République, provoquant un repli progressif sur l'Hexagone au détriment des outre-mer, où les abus se multiplient. Françoise Vergés s'interroge sur les causes et les conséquences de ces reconfigurations et sur la marginalisation de la question raciale et coloniale par les mouvements féministes actifs en métropole, en particulier le MLF. En s'appuyant sur les notions de genre, de race, de classe dans une ère postcoloniale, l'autrice entend faire la lumière sur l'histoire mutilée de ces femmes, héritée d'un système esclavagiste, colonialiste et capitaliste encore largement ignoré aujourd'hui.
Keywords: 1900-1999; 1960-1969; 1970-1979; afrique; approches et analyses; corps; cours; discours dominant; europe; fem3100; france; féminisme décolonial; lit4700; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; île de la réunion

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Black atlantic, queer Atlantic: Queer imaginings of the middle passage - Tinsley, Omise'eke Natasha (GLQ: A Journal of Lesbian and Gay Studies, 2008)
Qu'est-ce que cela signifierait pour les études queer et sur la diaspora africaine de théoriser que l'Atlantique noir a toujours été un Atlantique queer ? Quelle nouvelle géographie – ou mieux, océanographie – des identités sexuelles, genrées, transnationales et raciales pourrait émerger d'une lecture queer des dislocations transocéaniques entre l'Afrique et la Caraïbe ? Cet article examine la diaspora africaine canonique et les textes théoriques queer en dialogue avec des textes créatifs récemment publiés qui imaginent les relations queer entre les kidnappés africains dans les cales des navires négriers. Ces textes créatifs, selon moi, théorisent plus largement l'espace conceptuel à la fois pour repenser les histoires sexuelles et raciales submergées et pour commenter les intersections entre la diaspora africaine et les expériences queer à une époque contemporaine de réfugiés haïtiens, de travailleurs dominicains transnationaux, et des militants « homosexuels » antillais internationaux. Les textes examinés comprennent celui de Paul GilroyBlack Atlantic (1993), Gender Trouble de Judith Butler (1990), Erzulie's Skirt d'Ana-Maurine Lara (2006) et Map to the Door of No Return de Dionne Brand (2001).
Keywords: afrique; amériques; approches et analyses; caraïbes; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; premier cycle; queer; racisme; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Femmes et immigrées: corvéables à merci - Puech, Isabelle (Travail, genre et sociétés, 2006)
Dans le secteur des services, des milliers de femmes connaissent des formes d’exploitation salariale diffuses, peu visibles, socialement tolérées. Cet article propose de mettre en lumière un mode de gestion de la main-d’œuvre non qualifiée qui, sous couvert de flexibilité et de compression maximale des coûts, utilise les femmes les plus vulnérables sur le marché du travail – en particulier les femmes immigrées – comme variable d’ajustement. À partir d’une enquête de terrain menée auprès d’une population de femmes de chambre, l’article s’attachera à mettre au jour une face cachée des emplois précaires. Des emplois souvent à durée indéterminée qui ne protègent pas des conditions de travail pénibles, des temps de travail à rallonge, des salaires au rabais et des pratiques patronales frauduleuses.
Keywords: 1900-1999; 1970-1979; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; afrique subsaharienne; approches et analyses; capitalisme racial; corps; cours; discipline; europe; france; inégalités; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Garçon manqué - Bouraoui, Nina (Le livre de poche, 2000)
Dans les années 70, la guerre d'Algérie est encore dans tous les esprits. Ce récit autobiographique décrit la difficulté de vivre en Algérie avec une mère française, et de vivre en France avec un père algérien
Keywords: 1900-1999; 1970-1979; afrique; afrique du nord; algérie; approches et analyses; arts; cours; discipline; europe; france; lit2815; premier cycle; périodes historiques; racisme; roman; régions géographiques; système colonial; systèmes d'oppressions; études littéraires